Flip Book Innovation on Maglev Train Principles on Electromagnetic Induction Material to Grow Learning Motivation and Scientific Creativity - H Ruspitasari; W Munawaroh; S N Mahbubiyah Royani; Supeno Supeno (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
Scientific motivation and creativity are important components that must be developed in learning physics. Some research has been done to develop motivation and scientific creativity but still experience obstacles in the form of a lack of learning modules that can be used as a guide for students in independent learning. The author offers flip book innovations on the principles of the Maglev train on electromagnetic induction material to foster learning motivation and scientific creativity. This flip book consists of material and test instruments. The material covers the history of the Maglev train, parts of the Maglev train, the principles of the Maglev train, each of which is analyzed by Science, Technology, Engineering, Art and Mathematic. The results of this study are obtaining flip books on the subject of class XII electromagnetic induction to foster learning motivation and scientific creativity.